Ageing in migration or the test of the law. A geography of access to rights for elderly people born in North-West Africa and living in Aubervilliers. - (:unkn) unknown (My University, 2023)
The question of access to rights for elderly people born in North-West Africa and living in Aubervilliers is at the heart of this thesis. Part of the field of social and critical geography, it examines the test of rights through the prism of relations of domination and their spatial translations. Administered as foreigners, as workers and then retirees, and/or as poorly-housed people on precarious incomes, these people see major aspects of their lives and their daily lives as dependent on the administration and the law. They have to cope in a city where the administration of social services, the poor, foreigners and the elderly is marked by a concentration of constituents from the bottom of the social hierarchy. Our research, based mainly on social work and support for "access to rights" in the face of administrative procedures, sheds light on the links between the conditions of ageing, confrontation with the law and the relationship with space (at the time of the survey and over the long term of life trajectories). It's true that foreigners' rights enable them to settle in France to a certain extent, and social rights to a certain extent, covering risks (poverty, old age, illness, unemployment, etc.). However, making regularization, family reunification and freedom of movement conditional, and reducing access to resources to minimum levels, amounts to establishing an administrative/administrative relationship marked by subalternization and exclusion, throughout the process of aging. Through a cross-sectional study of access to entitlements and individual trajectories (residence-nationality, professional, residential, family, anchorage), the thesis attempts to unravel the tangle of conditions, times and spaces in which older, immigrant and administered people find themselves as they seek to access entitlements. The material is based on a field survey - carried out as a social worker and researcher - which combines several qualitative methods: particip
Keywords: African Research